2019
DOI: 10.1080/01621459.2019.1626242
|View full text |Cite
|
Sign up to set email alerts
|

MIMIX: A Bayesian Mixed-Effects Model for Microbiome Data From Designed Experiments

Abstract: Recent advances in bioinformatics have made high-throughput microbiome data widely available, and new statistical tools are required to maximize the information gained from these data. For example, analysis of high-dimensional microbiome data from designed experiments remains an open area in microbiome research. Contemporary analyses work on metrics that summarize collective properties of the microbiome, but such reductions preclude inference on the fine-scale effects of environmental stimuli on individual mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…This is therefore a type of partial technical process (Class IIa) as more of one transcript partially (not completely) inhibits our ability to measure another transcript. This competition to be counted has been successfully measured using multinomial based models [20,18,31]. As multinomial models model both this multivariate partial technical process (Class IIa) and sampling zeros (Class I) we consider multinomial models to be a hybrid of Class IIa and Class I models.…”
Section: Multivariate Count Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is therefore a type of partial technical process (Class IIa) as more of one transcript partially (not completely) inhibits our ability to measure another transcript. This competition to be counted has been successfully measured using multinomial based models [20,18,31]. As multinomial models model both this multivariate partial technical process (Class IIa) and sampling zeros (Class I) we consider multinomial models to be a hybrid of Class IIa and Class I models.…”
Section: Multivariate Count Modelsmentioning
confidence: 99%
“…Class II models go beyond modeling stochastic sampling by considering that zero values may arise due to secondary sources. Class IIa models, such as the multinomial-Dirichlet [17,11,12] or multinomial-logistic normal [18,19,20] based models represent sources of technical variation beyond stochastic sampling that can introduce zeros into the data. In contrast, class IIb models such as zero inflated models [18,21,22,23] or hurdle models [24,13], consider secondary sources of technical variation or bias that specifically add zero values into observed data.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that the expected negative covariance of feature proportions (truep→) in a Dirichlet distribution is a drawback that makes this distribution undesirable (Grantham, Guan, Reich, Borer, & Gross, ; Mandal et al, ; Weiss et al, ). Specifically, the elements of truep→ in a deviate from a Dirichlet distribution are expected to negatively covary (Mosimann, ) according to: Covpi,pj=-αiαjα02α0+1, where truep→ is the vector of expected proportions for features in the composition and trueα→ represents the Dirichlet parameter vector.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that the expected negative covariance of feature proportions (⃗ p) in a Dirichlet distribution is a drawback that makes this distribution undesirable (Grantham, Guan, Reich, Borer, & Gross, 2019). ; Mandal et al, 2015;Weiss et al, 2016).…”
Section: Additional Considerations Pertaining To Dirichlet-multinommentioning
confidence: 99%
“…3). Computational implementations of VI are a topic of current research 573 and will undoubtedly improve over coming years (Blei et al 2017 (Grantham et al 2017, Weiss et al 2016. Specifically, the elements of p in a deviate from a Dirichlet distribution are expected to negatively covary (Mosimann show two hypothetical compositions that differ between those sampling groups.…”
mentioning
confidence: 99%